High-performance flexible quasi-solid-state zinc-ion batteries with layer-expanded vanadium oxide cathode and zinc/stainless steel mesh composite anode - Zhao, Jin (2020)
Rechargeable aqueous zinc-ion batteries (ZIBs) featured with environmental friendliness, low cost, and high safety have attracted great interest but still suffer from the lack of high-performance electrodes. Herein, a facile in situ approach is developed to simultaneously introduce multivalence, increase the interlayer water content, and expand the interlayer distance in hydrated V2O5. These structural modulations endow the as-obtained layer-expanded V2O5 2.2H2O (E-VO) nanosheets with faster charge transfer kinetics, more Zn2+ storage space, and higher structural stability than precursor V2O5. Besides, a unique flexible Zn/stainless steel (Zn/SS) mesh composite anode with low polarization and uniform Zn stripping/plating behavior is fabricated, which alleviates the Zn dendrite growth. As cathode for aqueous ZIBs, E-VO exhibits high reversible capacity (450 mAh g-1 at 0.1 A g-1), good rate capability (222 mAh g-1 at 10 A g-1) and long stability (72% capacity retention for 3000 cycles at 5 A g-1). Moreover, the flexibility and large lateral size make E-VO a high-performance binder-free cathode for flexible quasi-solid-state Zn/E-VO battery, i.e. high capacity under different bending states (361 mAh g-1 at 0.1 A g-1), good rate capability (115mAh g-1 at 2 A g-1), and long stability (85% capacity retention for 300 cycles at 1 A g-1). The achievements of this study can be considered as an important step toward the development of aqueous-based ZIBs.